Black Sea wave energy atlas from 13 years hindcasted wave data - Aydogan, Burak; Ayat, Berna; Yuksel, Yalcin (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
The present study aims to evaluate the wave energy potential of the Black Sea. Wave properties were calculated using 3rd generation Spectral Wave Model for years 1996-2009 by using wind data from European Center for Medium-Range Weather Forecasts (ECMWF). The wave model was calibrated using the wave measurements conducted at five different stations. Wave power atlas displaying time averaged wave power for entire Black Sea was generated. Also wave power roses and wave power distribution tables in means of periods and heights for different regions were presented. Wave energy found to be decreasing along the coast from west to east. It was found that the most energetic region is the South Western part of the sea. The eastern part of the Black Sea is the least energetic in means of wave power. It was concluded that the most promising location is the Thracian shores of Turkey, especially west side of Istanbul. Beside this, other promising locations in the Black Sea Basin were also evaluated. Annual wave energies (kWh/m) for different regions were presented in this study. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Wave energy; Black Sea; Spectral wave modeling; ISLANDS; COAST; Science & Technology - Other Topics; Energy & Fuels